A Mediterranean-Based Ketogenic Diet Application Compared to a Calorie-Restricted Low-Fat Diet Application on Cardiometabolic Risk in Adults With Overweight or Obesity. (7th June 2021) - Falkenhain, Kaja; Locke, Sean; Lowe, Dylan; Reitsma, Nicholas; Weiss, Ethan; Little, Jonathan
Abstract: Objectives: To determine the effects of a Mediterranean-based ketogenic weight loss diet app paired with a breath acetone biofeedback device compared to a relevant comparator arm on blood biomarkers of cardiometabolic risk in a hands-off, real-world setting. Methods: Participants (N = 155) with overweight/obesity (41 ± 11 years, BMI = 32 ± 9 kg/m 2, 71% female) were randomized to one of two diet groups, with interventions delivered entirely via mobile app without in-person interaction with study staff: i) a Mediterranean-based ketogenic diet paired with a breath acetone biofeedback device (Keyto); or ii) a calorie-restricted low-fat diet (WW). Participants took daily weight measurements on an at-home wireless scale and a third-party laboratory obtained fasted blood samples at baseline and at 12 weeks. Results: Based on intention-to-treat analysis, participants in the Keyto group lost more weight than those in the WW group (−3.1 kg; 95% CI, −4.6 kg to −1.5 kg; P < 0.001). Likewise, those randomized to the Keyto app experienced greater improvements in markers of glycemic control (HbA1c; −0.2%; 95% CI, −0.3% to −0.1%; P < 0.001) and hepatic function (alanine aminotransferase, alkaline phosphatase, globulin; P < 0.01) compared to the WW group. In follow-up analyses accounting for baseline weight and change in body mass, the effects of group assignment on these cardiometabolic risk markers were found to remain significant independent of differences in weight loss between groups. No other differences in blood markers, including lipids and lipoproteins, were found. Conclusions: Among adults with overweight or obesity, assignment to the Keyto app, as compared to the WW app, resulted in greater weight loss and cardiometabolic improvements that appeared to be independent of weight loss. These findings suggest that a Mediterranean-based ketogenic diet app paired with a breath acetone biofeedback device is effective at improving cardiometabolic health beyond weight loss in a real-world setting. Funding Sources: Canadian Institutes of Health Research (CIHR), Michael Smith Foundation for Health Research (MSFHR), Mitacs Accelerate International with Keyto Inc. as the industry partner.